Розробка компонентів інформаційної системи магазину музичних інструментів - Сургай, А. А.; Міщеряков, А. Ю. (ХНУРЕ, 2025)
This work focuses on the design, development, and implementation of an information system for a musical instrument store, built on the ASP.NET Core platform. The store specializes in selling a wide range of musical instruments and sound equipment, and the system will enhance the customer experience by providing online access to the catalog, order management, automated report generation, and personalized product recommendations. By automating key processes, the system improves operational efficiency, reduces errors, while contributing to the store's overall business growth and customer satisfaction.
Keywords: магазин; музичний інструмент; система обліку